The Variability of Textural Properties and Drying Characteristics of Dehydrated Sewage Sludge - Sergio Luis Parra-Angarita; Mohamad Wael Al Sayed; Angélique Léonard (Clean Technologies, 2025)
This study investigates the drying behavior and rheological properties of dehydrated sewage sludge from various wastewater treatment plants in the Liege region (Belgium). Emphasizing the characterization of key parameters to enhance sludge management strategies, a series of experiments were conducted, including total solid content (TSC) determination, volatile solid content (VSC) analysis, texture profile analysis (TPA), penetrometry, and oscillatory rheology tests. Results showed no significant trends between specific evaporation capacity and the analyzed variables, cohesiveness, TSC, VSC, hardness, yield, and flow point. However, a clear trend indicated that higher G′ values are associated with improved drying rates. This aligns with the existing literature, suggesting that the viscoelastic properties of sludge, represented by G′, could potentially predict drying performance. A strong correlation between G′ and cohesiveness was also observed, recommending the use of G′ as the primary parameter due to the standardization and reliability of rheological tests. Despite the limited sample size, the study provides a valuable starting point for future research. Further investigations with larger sample sizes and controlled laboratory conditions are recommended to validate these findings and establish ranges within which the studied properties can be useful for future calculations and analyses. These efforts will contribute to optimizing sludge drying processes and promoting sustainable wastewater treatment practices.